Energy analysis of green office buildings in the tropics—Photovoltaic system - Yau, Y.H.; Lim, K.S. (Elsevier, 2016)
This research is to conduct energy analysis of green office buildings in the tropics. According to International Performance Measurement and Verification Protocol (IPMVP), there are four options available in the IPMVP, namely Option (A) Retrofit Isolation: Key Parameter Measurement, Option (B) Retrofit Isolation: All Parameter Measurement, Option (C) Whole Facility and Option (D) Calibrated Simulation. The current research is using Option (A) Retrofit Isolation: Key Parameter Measurement to study the Building Integrated Photovoltaic (BIPV) systems of Malaysia Green Technology Corporation (MGTC) Green Energy Office (GEO) Building. There are four types of BIPV systems being studied, namely System A (polycrystalline silicon), System B (amorphous silicon), System C (monocrystalline glass-glass, semi-transparent) and System D (monocrystalline silicon). The aims of the study are to examine the energy performance and quantify the energy savings of BIPV systems. The key parameters being evaluated are the system efficiency, reference yield, final yield, performance ratio and capacity factor. The methodology used is the actual data collection and analysis. The energy analysis result has shown that System B is having the best performance among all systems, whereas System C has the lowest performance.